The Palestinian Strategic Report 2009/10 - Ahmed Ibrahim, Hassan (Al-Zaytouna Centre, 2011)
This annual referential report, has become an essential classic in the academic realm of Palestinian Studies. It includes the latest and most recent statistical and analytic data on the various developments related to the Palestinian issue.